Banking trends in Europe today : lectures delivered at the 17th International Banking Summer School in the city of London and at Christ Church, Oxfort July 1964 (London : Institute of Bankers, 1964)
These lectures were delivered before an audience of bankers from fifty-two countries at the 17th international Banking Summer School in July 1964. The (I.B.S.S.) was originated by the institute of Bankers in order to provide a forum for free international discussion of practical financial problems.
Includes bibliographical notes p. 191
hza 27/11/2018
Loans
Keywords: Banks; Banking